Effects of repeated sprint training with progressive elastic resistance on sprint performance and anterior-posterior force production in elite young soccer players - Le Scouarnec, J.; Samozino, P.; Andrieu, B.; Thubin, T.; Morin, J. B.; Favier, F. B. (The Journal of Strength and Conditioning Research, 2022)
This study aimed to determine whether repeated sprint training with progressive high elastic resistance could improve sprint performance and anterior-posterior (AP) force production capacities of elite young soccer players. Seven elite U19 soccer players underwent 10 sessions of elastic-resisted repeated sprints on 8 weeks, whereas 8 U17 players from the same academy (control group) followed the same protocol without elastic bands. Sprint performance and mechanical parameters were recorded on a 30-m sprint before and after training. The control group did not show change for any of the measured variables. In contrast, the elastic-resisted training resulted in a significant improvement of the sprint time (-2.1 ± 1.3%; p = 0.026; Hedges' g = -0.49) and maximal velocity (Vmax; +3.9 ± 2%; p = 0.029; Hedges' g = 0.61) reached during the 30-m sprint. These enhancements were concurrent with an increase in the maximal power output related to AP force (Pmax; +4.9 ± 5.1%%; p = 0.026; Hedges' g = 0.42). Although the theoretical maximal AP force (F0) remained unchanged in both groups, there was a medium but nonsignificant increase in theoretical maximal velocity (V0; +3.7 ± 2.5%; p = 0.13; Hedges' g = 0.5) only in the elastic group. Therefore, the present results show that sprint capacity of elite young soccer players can be further improved by adding incremental resistance against runner displacement to raise the ability to produce AP force, rather at high velocity in the final phase of the acceleration.